2011
DOI: 10.1016/j.ajpath.2011.03.047
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Functions of Prostaglandin D2 in Murine Contact Hypersensitivity via DP and CRTH2

Abstract: Prostaglandin D2 (PGD2) exerts its effects through two distinct receptors: the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) and the D prostanoid (DP) receptor. Our previous study demonstrated that CRTH2 mediates contact hypersensitivity (CHS) in mice. However, the function of DP receptor remains to be fully established. In this study, we examine the pathophysiological roles of PGD2 using DP-deficient (DP ؊/؊ ) and CRTH2/DP-deficient (CRTH2 ؊/؊ / DP ؊/؊ ) mice to elucidate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
0
29
0
1
Order By: Relevance
“…Several groups reported its pro-inflammatory properties, where PGD 2 was shown to enhance the chemotactic activity of immune cells and to accumulate them in inflamed sites, causing the aggravation of OVA-induced asthma in mice or OVAinduced rhinitis in guinea pigs (9,10). In contrast, other groups reported that PGD 2 exerted anti-inflammatory properties, where it attenuated 2,4,6-trinitrochlorobenzene-induced contact hypersensitivity and zymosan-induced peritonitis in mice (11,12). Our group also showed that PGD 2 inhibits vascular permeability and inflammation in acute lung inflammation and implanted tumor models (13,14).…”
Section: Introductionmentioning
confidence: 95%
“…Several groups reported its pro-inflammatory properties, where PGD 2 was shown to enhance the chemotactic activity of immune cells and to accumulate them in inflamed sites, causing the aggravation of OVA-induced asthma in mice or OVAinduced rhinitis in guinea pigs (9,10). In contrast, other groups reported that PGD 2 exerted anti-inflammatory properties, where it attenuated 2,4,6-trinitrochlorobenzene-induced contact hypersensitivity and zymosan-induced peritonitis in mice (11,12). Our group also showed that PGD 2 inhibits vascular permeability and inflammation in acute lung inflammation and implanted tumor models (13,14).…”
Section: Introductionmentioning
confidence: 95%
“…24 Antagonists of CRTH2 ameliorate skin inflammation in IgE-mediated chronic skin responses, contact hypersensitivity and cedar pollen dermatitis in accordance with reduced numbers of dermal eosinophils. 20,21,25 Recent studies have identified indomethacin as a potent agonist of CRTH2, 26 causing PGD 2 -like and eotaxin (CCL11) -like responses in eosinophils. 27 These findings are somewhat inconsistent, offering clinical evidence that indomethacin is a useful therapeutic tool for EPF 3,4 and other eosinophilic skin diseases, such as angiolymphoid hyperplasia with eosinophilia 28 and recurrent cutaneous eosinophilic vasculitis.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…19 Prostaglandin D 2 promotes skin inflammation of IgE-mediated chronic skin responses and the elicitation phase of contact hypersensitivity. 20,21 Biological activities of PGD 2 are mediated by the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) and the D prostanoid receptor. These receptors are members of the G protein-coupled, seven transmembrane receptor family.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…PGD 2 elicits its downstream effects by activating 2 plasma membrane receptors, D prostanoid receptor 1 (DP1) (8) and chemoattractant receptorlike molecule expressed on Th2 cells (CRTH2), also known as DP2 (9). Activation of DP1 receptors is primarily associated with antiinflammatory effects (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). PGD 2 has also been shown to modulate inflammation, acting as either a proinflammatory or antiinflammatory mediator, depending on the pathologic condition and the affected tissue.…”
mentioning
confidence: 99%